ChemInform Abstract: Multicomponent Synthesis of Highly Functionalized Piperidines Using Sulfamic Acid as a Heterogeneous and Cost Effective Catalyst. Issue 45 (November 2015) - Patil, Dayanand; Chandam, Dattatray; Mulik, Abhijeet; Patil, Prasad; Jagdale, Suryabala; Deshmukh, Madhukar
Abstract The reaction is restricted to aromatic amines and aldehydes.